Embolization of Bleeding Pinna Arteriovenous Malformation after Ligation of the External Carotid Artery: A Therapeutic Challenge - Kumar, Rahul; Goyal, Ankur; Bhalla, Ashu Seith; Sandip, Sonia; Sikka, Kapil (Journal of Clinical Interventional Radiology ISVIR, 2017)
A 25-year-old patient presented with bleeding of right pinna arteriovenous malformation (AVM). There was history of ipsilateral external carotid artery (ECA) ligation 10 years back. Subsequent investigations (ultrasound, magnetic resonance imaging, digital subtraction angiography) showed recruitment of complex collaterals from the ipsilateral subclavian artery and vertebral artery feeding the recurrent nidus. The patient underwent two sessions of endovascular embolization and one session of percutaneous embolization. We wish to highlight the feasibility of antegrade embolization in such cases via collaterals and role of direct percutaneous treatment.
Keywords: arteriovenous malformation; external carotid artery ligation; head and neck